Astaxanthin composite nanoparticle as well as preparation method and application thereof

By using the co-precipitation method of oligopolymerization chitin oligosaccharide and zein protein, the problems of poor stability and low antioxidant activity of astaxanthin nanosystem in the prior art were solved, and efficient embedding and sustained release effects were achieved, and good market prospects were achieved.

CN119896316APending Publication Date: 2025-04-29JIANGSU ACAD OF AGRI SCI +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311413196.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, astaxanthin nanosystems have problems such as easy aggregation, poor stability, low antioxidant activity, difficult to control release in vivo, complex process and high production costs.

Method used

Astaxanthin composite nanoparticles were prepared by antisolvent coprecipitation method using oligopolymerization chitin oligosaccharide and zein, and nanoparticles were assembled as driving forces using hydrophobic, electrostatic and hydrogen bonds.

Benefits of technology

The embedding rate, loading, solubility, antioxidant activity and bioavailability of astaxanthin are improved, and the antioxidant functions of astaxanthin and chitosaccharides are synergistically synergistically integrated, and the operation is simple, economical and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896316A_ABST
    Figure CN119896316A_ABST
Patent Text Reader

Abstract

The invention discloses astaxanthin composite nanoparticles as well as a preparation method and application thereof, and belongs to the technical field of nano materials and food engineering. The astaxanthin composite nano-particles are formed by assembling astaxanthin, chitosan oligosaccharide and zein through an anti-solvent coprecipitation method by taking hydrophobic interaction, electrostatic interaction and hydrogen bonds as driving force. The astaxanthin composite nano-particles are high in astaxanthin loading capacity and encapsulation efficiency and very high in antioxidant activity, the water solubility and gastrointestinal tract slow release performance of the astaxanthin are remarkably improved, the bioavailability of the astaxanthin is improved, meanwhile, synergistic interaction of the antioxidant functions of the astaxanthin and the chitosan oligosaccharide is achieved, and the astaxanthin composite nano-particles are small in particle size and high in bioavailability. And the preparation method is simple and convenient, and has a good market application prospect in the fields of foods, medicines and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanomaterials and food engineering, and particularly relates to astaxanthin composite nanoparticles and a preparation method and application thereof. Background Art

[0002] Astaxanthin (AST) is a natural carotenoid that is widely distributed in marine and aquatic food raw materials such as shrimp, crab, and microalgae. It has stronger antioxidant activity than zeaxanthin, lutein, carotene, tocopherol, etc., and has multiple physiological and health benefits such as scavenging free radicals from the body, anti-cancer, preventing and treating cardiovascular and cerebrovascular diseases, lowering blood sugar, and delaying aging. Since astaxanthin cannot be synthesized in the body and can only be taken in through diet, its application in the fields of food, biomedicine, cosmetics, etc. has attracted much attention in recent years. The astaxanthin molecule contains 11 unsaturated conjugated double bonds, is highly hydrophobic, has poor stability, and is easily affected by light, oxygen, and heat and loses its activity. As a result, it has defects such as short gastrointestinal retention time, fast release rate, and low oral bioavailability, which seriously restricts the application of astaxanthin in the fields of food and medicine.

[0003] Utilizing food-grade nanoparticle delivery systems is an effective way to increase astaxanthin's stability, achieve its in vivo transport and slow release, and improve its bioavailability and bioactivity. It has been reported that soy protein, cyclodextrin, lactoferrin, lipids, and the like can be used as carriers to prepare microcapsules, nanoemulsions, liposomes, and the like for the encapsulation, loading, in vivo transport, and release of astaxanthin. However, natural proteins have limited loading capacity for astaxanthin, and existing technologies still face technical bottlenecks such as easy aggregation of astaxanthin nanosystems, poor stability, low antioxidant activity, difficulty in controlling in vivo release, complex processes, and high production costs. Therefore, different types of disassembly and reassembly of natural proteins through physical, chemical, and biological modification are still needed to improve the antioxidant activity of astaxanthin and its in vivo bioavailability.

[0004] Chitooligosaccharides (COS) are degradation products of chitosan. They are composed of oligosaccharides with a degree of polymerization of 2-20 and contain a large number of hydroxyl and amino groups. They have better water solubility and biological activity than chitosan. In particular, chitooligosaccharides with a degree of polymerization of 2-7 also have good blood-brain barrier penetration ability and have great application potential in functional foods and biomedicine. The present invention uses low-polymerization degree chitooligosaccharides and industrially produced zein (Zein) to prepare astaxanthin composite nanoparticles through an antisolvent coprecipitation method. This can achieve synergistic effects between astaxanthin and chitooligosaccharides in terms of water solubility, chemical stability, antioxidant function, and bioavailability. This is of great significance for promoting the industrial application of astaxanthin in the food, pharmaceutical, and cosmetic industries. It is also simple to operate, economical and practical, and has a very broad market prospect. Summary of the Invention

[0005] The present invention aims to address the deficiencies in the prior art and provide an astaxanthin composite nanoparticle and a preparation method thereof, wherein the nanoparticle improves the encapsulation efficiency, loading capacity, solubility, antioxidant activity, and bioavailability of astaxanthin, thereby achieving synergistic enhancement of the antioxidant functions of astaxanthin and chitosan oligosaccharides.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] The invention provides an astaxanthin composite nanoparticle. The astaxanthin composite nanoparticle is assembled from zein, chitosan oligosaccharide and astaxanthin by an anti-solvent co-precipitation method with hydrophobic interaction, electrostatic interaction and hydrogen bond as driving forces.

[0008] Disclosed are astaxanthin composite nanoparticles, wherein the average particle size of the composite nanoparticles is 70-120 nm and the potential is 33.3-46.5 mV.

[0009] The present invention also provides a method for preparing astaxanthin composite nanoparticles, comprising the following steps:

[0010] (1) Dissolve chitosan oligosaccharide in distilled water with a pH of 3 to 5, and then add anhydrous ethanol to obtain a chitosan oligosaccharide ethanol solution;

[0011] (2) mixing zein with the chitosan oligosaccharide ethanol solution obtained in step (1), stirring thoroughly, adjusting the zein concentration with anhydrous ethanol, and then adjusting the pH to 3-5 to obtain a protein-sugar mixture;

[0012] (3) dissolving astaxanthin in dichloromethane solvent, and then mixing it evenly with the protein-sugar mixture obtained in step (2), placing it in a magnetic stirrer at room temperature and stirring it at a speed of 500-1000 r / min for 20-40 minutes, then adding 1.5-3 times the volume of distilled water, mixing evenly, and then adjusting the pH to 3-5 to obtain an astaxanthin composite nanoparticle dispersion;

[0013] (4) The astaxanthin composite nanoparticle dispersion obtained in step (3) is subjected to rotary evaporation to remove ethanol, and then centrifuged to remove unreacted raw materials, and the supernatant is freeze-dried to obtain astaxanthin composite nanoparticles.

[0014] Preferably, in step (1), the degree of polymerization of the chitosan oligosaccharide is 2 to 7.

[0015] Preferably, in step (1), the concentration of chitosan oligosaccharide in the chitosan oligosaccharide ethanol solution is 0.5-2 mg / mL, and the final concentration of ethanol is 60%-90%.

[0016] Preferably, in step (2), the concentration of zein in the protein-sugar mixture is 10-25 mg / mL.

[0017] Preferably, in step (3), in the astaxanthin composite nanoparticle dispersion, the mass ratio of chitosan oligosaccharide, zein, and astaxanthin is 5-20:100:0.5-2.5.

[0018] The present invention also provides an application of the astaxanthin composite nanoparticles prepared by the above method in food, health products and medicines.

[0019] Preferably, the astaxanthin composite nanoparticles are used in the preparation of antioxidant functional foods and antioxidant drugs.

[0020] The astaxanthin composite nanoparticles prepared by the technology of the present invention have high antioxidant activity, and astaxanthin has a sustained-release property in the gastrointestinal tract. It has strong nutritional and health effects and huge market development potential.

[0021] Compared with the prior art, the advantages of the present invention are as follows:

[0022] 1) The nanoparticles prepared by the present invention are formed from zein, chitosan oligosaccharide, and astaxanthin through an antisolvent co-precipitation method. The stability of the nanoparticles is maintained by hydrogen bonding, electrostatic interaction, and hydrophobic interaction, thus overcoming the technical difficulties of simple zein loading of astaxanthin, such as weak interaction force, large particle size, poor stability, and low loading efficiency.

[0023] 2) The nanoparticles of the present invention have a high loading capacity and encapsulation efficiency for astaxanthin, improve the water solubility of astaxanthin, and have a sustained-release performance in the intestine that is significantly better than that of free astaxanthin. While improving the bioavailability of astaxanthin, they also achieve synergistic enhancement of the antioxidant functions of astaxanthin and chitosan oligosaccharides.

[0024] 3) The nanoparticles of the present invention have a small particle size (70-120 nm). Compared with large-sized nanoparticles, they have a larger specific surface area that can be modified with more ligands. They are also more likely to penetrate the blood-brain barrier to exert their nutritional and health benefits, have good drug delivery effects, and have great market development potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 These are Fourier transform infrared spectra of astaxanthin composite nanoparticles (ZCA-Nps), zein / chitosan oligosaccharide nanoparticles (ZC-Nps), and free astaxanthin (AST) prepared in Example 1.

[0026] Figure 2 The scanning electron microscopy (A) and transmission electron microscopy (B) images of the astaxanthin composite nanoparticles (ZCA-Nps) prepared in Example 1 are shown.

[0027] Figure 3 This is a graph showing the antioxidant capacity test results of astaxanthin composite nanoparticles (ZCA-Nps) and zein / chitosan oligosaccharide nanoparticles (ZC-Nps), free astaxanthin (AST), and vitamin C (VC) prepared in Example 3.

[0028] Figure 4 These are the release measurement results of the astaxanthin composite nanoparticles (ZCA-Nps) and free astaxanthin (AST) prepared in Example 3 in simulated gastrointestinal fluid. DETAILED DESCRIPTION

[0029] The following examples of the present invention are described in detail. It should be noted that these examples are descriptive and not restrictive, and should not be used to limit the scope of the present invention. Unless otherwise specified, all detection techniques and methods in the following examples are conventional methods; the test materials used in the following examples are all conventional chemical reagents and biochemical reagents.

[0030] Main materials and reagents: astaxanthin, chitosan oligosaccharide (Shanghai Aladdin Biochemical Technology Co., Ltd.); zein (Shanghai Yuanye Biotechnology Co., Ltd.); dichloromethane, anhydrous ethanol, sodium hydroxide, hydrochloric acid, sodium chloride, etc. (Sinopharm Chemical Reagent Co., Ltd., analytical grade reagents); DPPH free radical scavenging ability kit (Nanjing Jiancheng Bioengineering Institute).

[0031] Main instruments and equipment: rotary evaporator (Shanghai Xiande Experimental Instrument Co., Ltd.); magnetic stirrer (Shanghai Silu Instrument Co., Ltd.); refrigerated centrifuge (Hunan Xiangyi Laboratory Instrument Development Co., Ltd.); particle size-Zeta potential analyzer (Zetasizer Nano-ZS90, Malvern, UK); transmission electron microscope (Hitachi HT7700, Japan); desktop constant temperature oscillator (Tianjin Ounuo Instrument Co., Ltd.); microplate reader (Thermo Scientific Multiskan GO, USA); vacuum freeze dryer (Nanjing Zaizhi Automation Equipment Co., Ltd.); pH meter (Mettler Toledo Technology (China) Co., Ltd.).

[0032] Example 1

[0033] A preparation method of astaxanthin composite nanoparticles (the mass ratio of chitosan oligosaccharide, zein, and astaxanthin is 10:100:1) is as follows:

[0034] 1) Weigh 20 mg of chitosan oligosaccharide with a degree of polymerization of 2 to 7, dissolve it in 4 mL of distilled water with a pH of 4, and then add 16 mL of anhydrous ethanol to make the final concentration of ethanol 80%, to obtain a chitosan oligosaccharide ethanol solution with a concentration of 1 mg / mL.

[0035] 2) 200 mg of zein was mixed with the chitosan oligosaccharide ethanol solution, and the mixture was thoroughly stirred. The pH was then adjusted to 4 with 0.1 mol / L hydrochloric acid to obtain a protein-sugar mixture with a zein concentration of 10 mg / ml.

[0036] 3) Dissolve 2 mg of astaxanthin in 2 mL of dichloromethane, then mix thoroughly with the protein-sugar mixture. Stir on a magnetic stirrer at 800 rpm for 30 minutes at room temperature. Add two volumes of distilled water, mix thoroughly, and adjust the pH to 4 to obtain a composite nanoparticle dispersion.

[0037] 4) The composite nanoparticle dispersion obtained in step 3) was subjected to a rotary evaporator to remove ethanol, and then subjected to a refrigerated centrifuge at 4000 rpm for 10 min to remove unreacted raw materials. The supernatant was freeze-dried in a vacuum freeze dryer to obtain astaxanthin composite nanoparticles.

[0038] In this example, a gradient test was conducted on the amount of astaxanthin (AST) added in step 3), and the amount of astaxanthin added was set to 0.2, 0.5, 1.0, 1.5, and 2.0 mg, respectively, to obtain composite nanoparticles with different AST mass concentrations. The particle size (Size), potential (Zeta), and PDI value of the composite nanoparticles were measured, and the results are shown in Table 1. As can be seen from Table 1, the average particle size of the prepared AST composite nanoparticles is 70.25-93.09 nm, the potential is 33.344.4 mV, and the PDI is less than 0.16, indicating that the composite nanoparticles of the present invention have a small particle size, a narrow particle size distribution, and a stable nanoparticle state.

[0039] Table 1 Effects of different AST concentrations on the particle size, potential and PDI value of composite nanoparticles

[0040]

[0041] Example 2

[0042] Structural characterization of astaxanthin composite nanoparticles.

[0043] (1) Sample preparation

[0044] Preparation of astaxanthin composite nanoparticles (ZCA-Nps): same as Example 1.

[0045] Preparation of zein-chitosan oligosaccharide nanoparticles (ZC-Nps): The difference from Example 1 is that step 3) is omitted, and the zein-chitosan oligosaccharide ethanol solution obtained in step 2) is subjected to rotary evaporation, refrigerated centrifugation, and freeze-drying to prepare ZC-Nps.

[0046] (2) Detection method: Fourier transform infrared spectroscopy, circular dichroism spectrometer, scanning electron microscopy and transmission electron microscopy were used to characterize ZCA-Nps, ZC-Nps and free AST, and their microstructure and interaction force were analyzed.

[0047] (3) Test results and analysis

[0048] From the infrared spectrum detection chart ( Figure 1 ), it can be seen that compared with the OH stretching vibration absorption band of ZC-Nps and the OH stretching vibration absorption band of AST, the OH stretching vibration absorption band (3284.13 cm-1) of the ZCA-Nps of the present invention is shifted, indicating that hydrogen bonds are formed between zein, chitosan oligosaccharides and astaxanthin; the CN stretching vibration and NH bending vibration absorption peaks (2931.23 cm-1) in ZCA-Nps are also shifted, indicating that there is an electrostatic interaction force during the assembly of nanoparticles. The characteristic absorption band of AST in ZCA-Nps almost disappears, indicating that AST is wrapped in the hydrophobic area of ​​the composite nanoparticles. From Figure 2 It can be seen from the figure that the composite nanoparticles prepared by the present invention are basically spherical in structure.

[0049] The conformational changes of zein in ZCA-Nps and ZC-Nps were detected by circular dichroism spectroscopy. As shown in Table 2, after the addition of AST, the α-helix and random coil contents of zein increased significantly, while the β-sheet content decreased, indicating that there was an intermolecular force between zein and AST, which caused the conformation of Zein to partially unfold and ultimately affected the secondary structure of Zein.

[0050] In summary, the ZCA-Nps of the present invention is assembled by the hydrophobic interaction, electrostatic interaction, and hydrogen bonding between zein, chitosan oligosaccharide, and astaxanthin as the driving force.

[0051] Table 2 Effect of astaxanthin on the secondary structure of zein

[0052]

[0053] Example 3

[0054] A preparation method of astaxanthin composite nanoparticles (the mass ratio of chitosan oligosaccharide, zein, and astaxanthin is 5:100:2) is as follows:

[0055] 1) Weigh 10 mg of chitosan oligosaccharide with a degree of polymerization of 2 to 7, dissolve it in 1 mL of distilled water with a pH of 4, and then add 4 mL of anhydrous ethanol to make the final concentration of anhydrous ethanol 80%, to obtain a chitosan oligosaccharide ethanol solution with a concentration of 2 mg / mL.

[0056] 2) Mix 200 mg of zein with the chitosan oligosaccharide ethanol solution, adjust the zein concentration with anhydrous ethanol, stir thoroughly, and then adjust the pH to 5 with 0.1 mol / L hydrochloric acid to obtain a protein-sugar mixture with a zein concentration of 20 mg / mL.

[0057] 3) Dissolve 4 mg of astaxanthin in 2 mL of dichloromethane, then mix thoroughly with the protein-sugar mixture. Stir on a magnetic stirrer at 1000 rpm for 50 minutes at room temperature. Add 3 times the volume of distilled water, mix thoroughly, and adjust the pH to 4 to obtain a composite nanoparticle dispersion.

[0058] 4) The composite nanoparticle dispersion obtained in step 3) was subjected to a rotary evaporator to remove ethanol, and then subjected to refrigerated centrifugation at 4000 rpm for 10 min to remove unreacted raw materials. The supernatant was freeze-dried in a vacuum freeze dryer to obtain astaxanthin composite nanoparticles.

[0059] In this example, the thermal stability, pH stability, and salt stability of astaxanthin composite nanoparticles were tested.

[0060] Thermal stability test: Place 10 mL of the composite nanoparticle dispersion obtained in step 3) in a test tube and place in a water bath at 30, 40, 50, 60, 70, and 80°C for 3 hours. After the sample cools to room temperature, measure its particle size, potential, and PDI.

[0061] pH stability test: The composite nanoparticle dispersion obtained in step 3) was adjusted to different pH values ​​(2, 3, 4, 5, 6, 7, 8, 9, 10, and 11) using 0.1 M HCl or 0.1 M NaOH. After overnight storage at 4°C, the particle size, potential, and PDI of the samples were measured.

[0062] Salt stability test method: Astaxanthin composite nanoparticles were evenly mixed with a certain concentration of NaCl solution to prepare astaxanthin composite nanoparticle dispersions containing different NaCl concentrations (0, 5, 10, 20, 30, 40, 50, 100 mmol / L). After storing in a 4°C refrigerator overnight, the particle size, potential and PDI of the samples were measured.

[0063] It can be seen from the test results in Tables 3 to 5 that heat treatment at 30 to 80°C will not destroy the stability of astaxanthin nanoparticles; except for being unstable under pH 6, astaxanthin composite nanoparticles can maintain stability in a wider pH range; in the salt ion concentration range of 0 to 50 mmol / L, astaxanthin nanoparticles can maintain a relatively stable state.

[0064] Table 3 Effect of temperature on the stability of astaxanthin nanoparticles

[0065]

[0066] Table 4 Effect of pH on the stability of astaxanthin nanoparticles

[0067]

[0068] Table 5 Effect of salt concentration on the stability of astaxanthin nanoparticles

[0069]

[0070] Example 4

[0071] Evaluation of antioxidant activity of astaxanthin composite nanoparticles.

[0072] (1) Sample preparation

[0073] Preparation of astaxanthin composite nanoparticles (ZCA-Nps): same as Example 3.

[0074] Preparation of zein-chitosan oligosaccharide nanoparticles (ZC-Nps): The difference from Example 1 is that step 3) is omitted.

[0075] (2) Measurement method

[0076] DPPH radical scavenging ability assay: 1 mL of a 1 mg / L ZCA-Nps solution, ZC-Nps solution, free AST solution, and VC solution were placed in graduated test tubes. 1 mL of a 0.2 mmol / L DPPH solution was added. The mixture was shaken thoroughly and incubated in the dark for 30 minutes. The supernatant was collected and the absorbance at 517 nm was measured using an automated microplate reader. The DPPH radical scavenging rates of ZCA-Nps, ZC-Nps, AST, and VC were calculated according to the following formula.

[0077] DPPH free radical scavenging rate (%) = [1-(A1-A2) / A0] × 100%

[0078] Where: A1 is the absorbance of the test group; A2 is the absorbance of the control group; A0 is the absorbance of the blank group.

[0079] Total antioxidant capacity (FRAP) assay: 0.2 mL of ZCA-Nps, ZC-Nps solution, free AST solution, and VC solution were mixed with 1.8 mL of FRAP (acetate buffer (300 mmol / L, pH 3.6), TPTZ (10 mmol / L), and ferric chloride (20 mmol / L) at a ratio of 10:1:1 (v / v). The mixture was then incubated in a 37°C water bath for 10 min. The absorbance was measured at a wavelength of 593 nm using an automatic microplate reader. A standard curve was drawn using different concentrations of FeSO4 instead of the sample. According to the standard curve equation (Y = 0.0125X + 0.0617, R 2 =0.999) to calculate the total antioxidant capacity of the samples.

[0080] (3) Test results

[0081] The DPPH free radical scavenging rate and FRAP test results in the samples are shown in Figure 3 .Depend on Figure 3 It can be seen that due to its low solubility, free AST cannot fully combine with free radicals, resulting in low antioxidant capacity. The antioxidant activity of ZCA-Nps at the same concentration is much higher than that of ZC-Nps and free AST, and even higher than the DPPH free radical scavenging rate and total antioxidant capacity (FRAP) of VC at the same concentration. This shows that the astaxanthin composite nanoparticles of the present invention have high antioxidant activity, can greatly improve the solubility of astaxanthin, and can also achieve synergistic enhancement of the antioxidant activity of astaxanthin and chitosan oligosaccharides. It can be used as a high-quality raw material for antioxidant foods, medicines, and health products.

[0082] Example 5

[0083] Controlled release and bioaccessibility analysis of astaxanthin from astaxanthin composite nanoparticles.

[0084] (1) Preparation of astaxanthin composite nanoparticle dispersion, same as in Example 3.

[0085] (2) Detection method:

[0086] Prepare simulated gastric fluid (SGF): mix 3.84 mL of hydrochloric acid, 800 mL of distilled water, and 10 g of pepsin, adjust the pH to 2.0, and then dilute to 1000 mL to obtain SGF.

[0087] Prepare simulated intestinal fluid (SIF): dissolve 6.8 g of potassium dihydrogen phosphate in 500 mL of purified water, adjust the pH to 6.8 with 0.1 mol / L sodium hydroxide solution, add 200 mL of 5% pancreatin aqueous solution, and adjust the volume to 1000 mL to obtain SIF.

[0088] Determination: Take 20 mL of astaxanthin composite nanoparticle dispersion, add 20 mL of SGF, stir at 37°C and 300 r / min for 2 hours, take 2 mL every hour and place it in a refrigerated centrifuge, centrifuge at 4000 rpm / min for 10 minutes, and use the same concentration of free astaxanthin as a control to measure the astaxanthin release rate in the supernatant; take 30 mL of the composite nanoparticle dispersion after digestion, add 7.5 mL of SIF, stir at 37°C and 300 r / min for 4 hours, and use the same concentration of free astaxanthin as a control, measure every hour and calculate the astaxanthin release rate according to the following formula, where the astaxanthin release rate after digestion is the bioaccessibility of astaxanthin.

[0089] Release rate / % = astaxanthin content in supernatant / total astaxanthin × 100%

[0090] (3) Test results and analysis

[0091] Astaxanthin release rate determination results are shown in Figure 4 .Depend on Figure 4 It can be seen that astaxanthin composite nanoparticles are relatively stable during the first 2 hours of gastric juice digestion, with only a small amount of astaxanthin released. After entering the intestine, astaxanthin begins to be released slowly, while free astaxanthin can be detected at the beginning of the experiment. During the digestion process, the release amount decreases due to the unstable nature of astaxanthin. After the simulated digestion of gastrointestinal fluid, the astaxanthin release rate in the composite nanoparticles is 38.36% higher than that of free astaxanthin, indicating that astaxanthin composite nanoparticles can achieve targeted release of astaxanthin in the human intestine, have higher bioaccessibility, and can be better absorbed and utilized.

[0092] In summary, the astaxanthin composite nanoparticles prepared by the present invention have good stability, high antioxidant activity, can significantly improve the solubility of astaxanthin and its controlled release performance in the gastrointestinal tract, and have obvious advantages.

[0093] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. An astaxanthin composite nanoparticle, characterized in that: The astaxanthin composite nanoparticles are assembled from zein, chitosan oligosaccharide and astaxanthin by an anti-solvent co-precipitation method using hydrophobic interaction, electrostatic interaction and hydrogen bonding as driving forces.

2. The astaxanthin composite nanoparticle according to claim 1, characterized in that: The average particle size of the composite nanoparticles is 70-120 nm, and the potential is 33.3-46.5 mV.

3. The method for preparing astaxanthin composite nanoparticles according to claim 1 or 2, characterized in that: The following steps are involved: (1) dissolving chitosan oligosaccharide in distilled water with a pH of 3 to 5, and then adding anhydrous ethanol to obtain a chitosan oligosaccharide ethanol solution; (2) mixing zein with the chitosan oligosaccharide ethanol solution obtained in step (1), stirring them evenly, adjusting the concentration of zein with anhydrous ethanol, and then adjusting the pH to 3-5 to obtain a protein-sugar mixture; (3) dissolving astaxanthin in a dichloromethane solvent, and then mixing it evenly with the protein-sugar mixture obtained in step (2), placing it in a magnetic stirrer at room temperature and stirring it at a speed of 500 to 1000 r / min for 20 to 40 minutes, then adding 1.5 to 3 times the volume of distilled water, mixing evenly, and then adjusting the pH to 3 to 5 to obtain an astaxanthin composite nanoparticle dispersion; (4) The astaxanthin composite nanoparticle dispersion obtained in step (3) is subjected to rotary evaporation to remove ethanol, and then centrifuged to remove unreacted raw materials, and the supernatant is freeze-dried to obtain astaxanthin composite nanoparticles.

4. The method for preparing astaxanthin composite nanoparticles according to claim 3, characterized in that: In step (1), the polymerization degree of the chitosan oligosaccharide is 2 to 7.

5. The method for preparing astaxanthin composite nanoparticles according to claim 3, characterized in that: In step (1), in the chitosan oligosaccharide ethanol solution, the concentration of chitosan oligosaccharide is 0.5-2 mg / mL, and the final concentration of ethanol is 60%-90%.

6. The method for preparing astaxanthin composite nanoparticles according to claim 3, characterized in that: In step (2), the concentration of zein in the protein-sugar mixture is 10-25 mg / mL.

7. The method for preparing astaxanthin composite nanoparticles according to claim 3, characterized in that: In step (3), in the astaxanthin composite nanoparticle dispersion, the mass ratio of chitosan oligosaccharide, zein, and astaxanthin is 5-20:100:0.5-2.

5.

8. Use of the astaxanthin composite nanoparticles according to any one of claims 1 to 7 in food, health products and medicines.

9. The use according to claim 8, characterized in that: The astaxanthin composite nanoparticles are used in the preparation of antioxidant functional foods and antioxidant drugs.

Citation Information

Cited By

  • Zeaxanthine nanoparticles as well as preparation method and application thereof

    CN120919081A